2015
DOI: 10.1002/lsm.22354
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of yellow tattoo ink with a novel 532‐nm picosecond laser

Abstract: This is the first case series that demonstrates effective and consistent reduction of yellow tattoo ink using a frequency doubled Nd:YAG 532-nm laser with a picosecond pulse duration. Treatments were well tolerated and subjects had positive outcomes. This is a small observational case series from an ongoing clinical trial, and studies with a larger sample size and comparative group are needed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 10 publications
3
57
1
8
Order By: Relevance
“…In a comparative study on the use of 1064-nm picosecond-domain lasers for the removal of black ink tattoos [15], 90-100 % clearance rates were observed in 2/16 patients treated during four sessions with the picosecond-domain laser compared to none of the patients treated with the nanosecond laser [15]. Others reported that one to five treatments with the frequencydoubled 1064/532-nm picosecond-domain laser cleared 90-100 % of yellow ink tattoos in four of the six patients (67 %) [19]. A second trial [17] with the frequency-doubled laser at the same wavelength reported an average 91.6 ± 5.4 % clearance of black pigment after up to seven sessions.…”
Section: -100 % Clearancementioning
confidence: 82%
See 3 more Smart Citations
“…In a comparative study on the use of 1064-nm picosecond-domain lasers for the removal of black ink tattoos [15], 90-100 % clearance rates were observed in 2/16 patients treated during four sessions with the picosecond-domain laser compared to none of the patients treated with the nanosecond laser [15]. Others reported that one to five treatments with the frequencydoubled 1064/532-nm picosecond-domain laser cleared 90-100 % of yellow ink tattoos in four of the six patients (67 %) [19]. A second trial [17] with the frequency-doubled laser at the same wavelength reported an average 91.6 ± 5.4 % clearance of black pigment after up to seven sessions.…”
Section: -100 % Clearancementioning
confidence: 82%
“…Seven trials explored the use of either 1064 nm (Nd:YAG) [15], 755 nm [16,18,20], 795 nm [13], 758 nm [14], or frequency-doubled 1064/532 nm [17] lasers for the treatment of mainly black and blue tattoos. One of the trials explored the use of frequency-doubled 1064/532-nm lasers for the treatment of yellow tattoos [19]. One trial [15] used a laser with a pulse duration of 35 ps, while the rest of the trials used lasers with pulse durations of 350-900 ps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Генерирование оптических гармоник, в свою очередь, необходимо для получения излучения в спектре, отличном от излучения накачки. Например, вторая гармоника Nd:YAG лазера имеет длину волны 532 нм и широко используется в спектроскопии, медицине, голографии, а также при создании стандартов частоты [1]. Стабильные по частоте лазеры широко используются не только в научных исследованиях, но и в технике как эталонные источники света для интерферометрических измерений длины.…”
Section: Introductionunclassified